Prescription for heterosexuality : sexual citizenship in the cold war era - Lewis, Carolyn Herbst (University of North Carolina Press, 2010)
In this lively and engaging work, Carolyn Lewis explores how medical practitioners, especially family physicians, situated themselves as the guardians of Americans' sexual well-being during the early years of the Cold War. She argues that many doctors believed that a satisfying sexual relationship with very specific attributes and boundaries was the foundation of a successful marriage, a fundamental source of happiness in the American family, and a crucial building block of a secure nation. Drawing on hundreds of articles and editorials in medical journals as well as other popular and professi.